Functional connectivity analysis of patients with temporal lobe epilepsy displaying different ictal propagation patterns*. Issue 5 (24th November 2020) - Sirin, Nermin Gorkem; Kurt, Elif; Ulasoglu‐Yildiz, Cigdem; Kicik, Ani; Bayram, Ali; Karaaslan, Zerrin; Bebek, Nerses; Baykan, Betul; Demiralp, Tamer; Gurses, Candan
Abstract: Aims The pathophysiology of switch‐of lateralization and bilateral temporal asynchrony, which are scalp EEG ictal propagation patterns (iPP) in temporal lobe epilepsy (TLE), is poorly understood. We aimed to analyse functional connectivity (FC) of the temporal lobe and related areas in patients with TLE with iPP (iPP‐TLE) and without iPP (non‐iPP TLE). Methods Twelve patients with iPP‐TLE, 13 patients with non‐iPP TLE, and 13 healthy controls (HC) underwent resting‐state functional MRI (fMRI). Seed‐based FC was analysed between the homologous insulae, hippocampi, amygdalae, parahippocampal, superior temporal, and middle temporal gyri. Results FC was reduced between homologous temporal lobe areas in patients with TLE compared with HCs. Patients with non‐iPP TLE displayed decreased FC between the homologous parahippocampal and superior temporal gyri, and patients with iPP‐TLE had lower FC between the homologous insulae, parahippocampal and superior temporal gyri compared with HC. Furthermore, patients with iPP‐TLE tended to have lower FC between the bilateral insulae when compared with patients with non‐iPP TLE. Conclusions Reduced FC of interhemispheric connections between temporal lobes and related areas might be an adaptive change to protect contralateral areas in seizure propagation. The insula showed decreased FC between two hemispheres in patients with iPP‐TLE, assuming a role in ictal scalp propagation pattern changes in TLE.